2015
DOI: 10.1021/acssuschemeng.5b00453
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine-Based Nitrogen, Phosphorus, and Silicon Tri-doped Carbon for Supercapacitor Applications

Abstract: This paper reports the synthesis of N, P, and Si tri-doped C (NPSiDC) using thiamine (a renewable resource material), silicone fluid, and ammonium polyphosphate. A one-pot microwave assisted method was utilized in synthesizing NPSiDC. The method is simple, rapid, and economical which does not employ any inert or reducing gases. Three variants of NPSiDCs were synthesized by varying the proportions of the precursor materials. NPSiDC-1 was found to have high specific surface area of 471 m 2 g −1 and a single poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…45 Fig. 46,47 This result demonstrates that the energy storage capability of all the electrode materials originates mainly from Faradic reaction on the surface of Ni 2 CO 3 (OH) 2 . Meanwhile, the TEM image in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…45 Fig. 46,47 This result demonstrates that the energy storage capability of all the electrode materials originates mainly from Faradic reaction on the surface of Ni 2 CO 3 (OH) 2 . Meanwhile, the TEM image in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…This indicates that surface functionalities of TEAPNDC‐1 and TEAPNDC‐2 are participating in redox reactions with the electrolyte. TEAPNDC‐2 has the highest percent composition of quinone (6.86%) and pyridinic (2.45%) surface functionalities that are known to participate in the redox reactions influencing capacitance performance in acidic electrolyte . It is observed that MOLPNDC‐1 and MOLPNDC‐2 display very high surface areas with lower surface elemental compositions, indicating that EDL formation is playing a larger role in the capacitive performance of molasses‐based PNDCs.…”
Section: Data Analysis/resultsmentioning
confidence: 99%
“…TEAPNDC-2 has the highest percent composition of quinone (6.86%) and pyridinic (2.45%) surface functionalities that are known to participate in the redox reactions influencing capacitance performance in acidic electrolyte. [65] It is observed that MOLPNDC-1 and MOLPNDC-2 display very high surface areas with lower surface elemental compositions, indicating that EDL formation is playing a larger role in the capacitive performance of molasses-based PNDCs. Pore size is also a key factor in the performance of these materials; molasses-based materials show a pore size of ∼ 3 nm which is suitable for interaction with ions in acidic media.…”
Section: Electrochemical Studies In 6 M Kohmentioning
confidence: 93%
“…10 shows an illustration of possible types of ionic interactions that can occur between the surface nitrogen functionalities (N6/N5) and the ions in the acidic and basic media during potential cycling, which in turn explain the pseudocapacitive contribution of the nitrogen moieties in these materials. 19,61 In contrast, the CV curve recorded for NCM (MDE) -800 in neutral electrolyte (0.5 M Na 2 SO 4(aq) ) exhibits the double layer capacitance with the absence of redox peaks. Moreover, NCM (MDE) -800 achieves higher current density in 1 M H 2 SO 4(aq) compared to 6 M KOH (aq) , while the lowest current density is observed in 0.5 M Na 2 SO 4(aq) electrolyte.…”
Section: 76mentioning
confidence: 96%
“…It can be seen that the shapes of the isotherms were nearly identical for all NCM (MDE) -X materials and can be categorized as type IV with a characteristic type H4 hysteresis loop at p/p o > 0.4, which is indicative of the presence of micropores and mesopores. 60,61 The nearly linear middle portion in these isotherms signies multilayer adsorption, while the hysteresis shows capillary condensation in the mesopores. 62 Interestingly, in NCM (MDE) -700, the steep region of the desorption branch reached a non-closure point at lower relative pressure, indicating irreversible interaction between N 2 and the absorbent.…”
mentioning
confidence: 98%